2000
DOI: 10.1007/s001270050279
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of contact with psychiatric services: immigrant and Australian-born patients

Abstract: The commonly reported underrepresentation of immigrant groups in the psychiatric service system does not appear to be due to greater discontinuation of contact with services. If the assumption of equal community prevalence of disorder is made, then the observed under-representation may be due to differential rates of access to (that is, initial contact with) psychiatric services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 0 publications
3
27
1
2
Order By: Relevance
“…Based on an analysis of the 2001 Victorian Census data and records of contacts with Victorian mental health services for individuals across the state between 2004and 2005, Stolk et al (2008 determined that whilst approximately 20 per cent of the population was born in non-English-speaking countries (NESC), NESC mental health service users comprised only 13 per cent of community clients and 15 per cent of inpatients. These findings are consistent with research in other settings that has demonstrated lower rates of access and lower rates of treated prevalence for individuals from CaLD backgrounds (Bhugra, 2004;Harrison et al, 2001;Klimidis et al, 2000;Stolk et al, 2008). It is now recognised that individuals from CaLD backgrounds may not access mental health services in multicultural western communities because of a range of factors.…”
Section: Introductionsupporting
confidence: 93%
“…Based on an analysis of the 2001 Victorian Census data and records of contacts with Victorian mental health services for individuals across the state between 2004and 2005, Stolk et al (2008 determined that whilst approximately 20 per cent of the population was born in non-English-speaking countries (NESC), NESC mental health service users comprised only 13 per cent of community clients and 15 per cent of inpatients. These findings are consistent with research in other settings that has demonstrated lower rates of access and lower rates of treated prevalence for individuals from CaLD backgrounds (Bhugra, 2004;Harrison et al, 2001;Klimidis et al, 2000;Stolk et al, 2008). It is now recognised that individuals from CaLD backgrounds may not access mental health services in multicultural western communities because of a range of factors.…”
Section: Introductionsupporting
confidence: 93%
“…Regarding the longer length of stay in our hospital of immigrant patients, most studies worldwide did not find a difference between immigrants and the national majority (Iversen & Morken, 2003;Klimidis, McKenzie, Lewis, & Minas, 2000;Shaikh, 1985), but also shorter (Alda Díez et al, 2010;Lay et al, 2006) and longer (Trauer, 1995) lengths of stay have been reported for immigrants. These variations in findings might be due to wide differences in mental health and social systems.…”
Section: Discussionmentioning
confidence: 89%
“…Studies in the United States and Australia demonstrate that many minorities do, in fact, seek help for mental illness less frequently than the majority group. [57][58][59][60][61] Therefore, it may be the case that francophone minorities would be less likely to use health care services than anglophones and francophones in the majority. Regarding differences in service use between Quebec and other provinces, Vasiliadis et al, 62 who based their study on CCHS 1.2 data, did not find the province of residence to be a contributing factor in services use in general, nor did they find differences between Quebec and the rest of Canada overall for FP service use.…”
Section: Discussionmentioning
confidence: 99%